Integrating Academic Information System Based on Enterprise Architecture using ETL: A Case Study of SIUNU Using the TOGAF ADM Framework - Fauzi, Cholid; Pribadi, Didik S; Rifan, Muhammad; Fauziyyah , Fasya Nur; Fadillah, Arsal (Riviera Publishing, 2026)
Nahdlatul Ulama University, which manages multiple institutions, requires an integrated information system to coordinate academic and administrative processes efficiently. However, developing such a system faces challenges related to business process complexity and the need for diverse user role distribution. This study aims to design an integrated academic information system (SIUNU) by combining BPMN business process modeling and RACI matrix analysis to produce a modular, scalable, and accountable system architecture in a multi-campus environment. The research employs a qualitative-descriptive methodology with a case study approach. Business process modeling was conducted using Business Process Model and Notation (BPMN) 2.0 to visually represent workflows. The research produced business process models for five main modules: Authentication (login, forgot password, logout), Academic Dashboard (student data, lecturer data, GPA summaries, tracer studies), Evaluation and Reporting (teaching evaluation), Letter Management (drafting, verification, disposition, archiving), and the MBKM Module (program registration, credit conversion). RACI analysis generated structured role mapping, showing the Super Admin as the primary accountable party for system configuration, PTNU Admin as the operational implementer, Lecturers as academic consultants, and Students as active users of personal data. The integration of BPMN and RACI proved effective in producing an academic information system design framework that is not only technically robust but also organizationally accountable. This research contributes to the development of academic information system literature through an integrative approach and provides a ready-to-implement design for Nahdlatul Ulama University.